PENGARUH HARGA, ATRIBUT PRODUK DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN ROKOK GUDANG GARAM DI KECAMATAN PEDURUNGAN - Jaelani Sidik, 07.05.51.0107; Setiawan, Mulyo Budi (Students Journal of Economic and Management, 2012)
Level emulation of corporate world in Indonesia very tight, because each company ever can improve market compartment and reach for new consumer. Company have to earn to determine correct marketing strategy to be its effort can stay and win emulation, so that the intention of the company can reach. Producer shall have knowledge consumer appetite related to price, product attribute and advertisement which good for knowing how third the factor can influence consumer in buying Gudang Garam cigarette. Target of this research is to know influence of price, product attribute, and advertisement to decision of purchasing of Gudang Garam cigarette in District of Pedurungan. Population in this research is all society exist in district of Pedurungan, while sampel the taken is counted 100 responder with method of convenience samples (election of sampel pursuant to amenity), that is method chosen sampel of population element which data is easy to got by researcher. As for analysis method the used is examination of data instrument, analyse doubled linear regresi, examination of hypothesis t-test and coefficient of determinasi. From calculation of t hitung price variable (X1) known by number of t hitung = 4,932 > t tables of 1,661 so that signifikan. Matter this means price have an effect on positive and signifikan to decision of proven purchasing. From calculation of t hitung product attribute variable (X2) known by number of t hitung = 3,363 > t tables of 1,661 so that signifikan. Matter this means product attribute have an effect on positive and signifikan to decision of proven purchasing. From calculation of t hitung advertisement variable (X3) known by number of t hitung = 3,278 > t tables of 1,661 so that signifikan. Matter this means advertisement have an effect on positive and signifikan to decision of proven purchasing. Result of analysis go into effect for all population (entire/all society). Key words : Price, Attribute Product, Advertisement, Decision of Purchasing.